PENGARUH SISTEM PELAPORAN DAN PENGENDALIAN INTERNAL TERHADAP TRANSPARANSI PENGELOLAAN DANA DESA DI DESA LENGKONG, KECAMATAN BOJONGSOANG PADA MASA PANDEMI COVID-19 - Kartini, Neneng (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
By using a descriptive quantitative research approach, this study intends to determine the effect of the Reporting System and Internal Control on the Transparency of Village Fund Management in Lengkong Village, Bojongsoang District. Multiple linear regression analysis was used to analyze the data in this study. According to research findings, the Reporting System has no statistically significant effect, with the t-test results of 0.112 and sig. 0.605 > = 0.05. This has provided evidence that financial reporting in Lengkong Village is in accordance with siskeudes rules, while Internal Control has a major effect on Transparency in Village Fund Management, with t test results of 0.385 and sig. 0.001 = 0.05. It is understandable that internal control is improving.